2021
DOI: 10.9734/ejmp/2021/v32i330380
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of NaCl-Induced Stress in Tomato (Lycopersicon esculentum L.)

Abstract: Comparative study about the salt-induced oxidative stress and lipid peroxidation has been realised in primary root tissues for Tomato (Lycopersicon esculantum L.) in order to evaluate their responses to salt stress. Salinity impacts in terms of root growth, H2O2 generation, lipid peroxidation and membrane destabilisation were more pronounced in roots. Salt treatment in form of NaCl was given to the roots of the tomato plants in hydroponics culture. Root length was measured by centimetre scale, H2O2 and lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, a number of studies have shown clear correlation between tomato salt tolerance under in In vitro evaluation of tomato genotypes for salt tolerance has undoubted advantages (high productivity, as well as stability and reproducibility of the obtained experimental data due to the maintenance of constant controlled conditions) in comparison with openfield system and pot experiments (Figure 9). The authors cultivated seeds [21][22][23], shoot apexes [48], shoot apical meristem [49], and callus [50][51][52][53] as an explant source under salinity treatments in vitro. The disadvantage of seeds as an explant source is high heterogeneity, as well as greatly differ in the uniformity of germination capacity and germination energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of studies have shown clear correlation between tomato salt tolerance under in In vitro evaluation of tomato genotypes for salt tolerance has undoubted advantages (high productivity, as well as stability and reproducibility of the obtained experimental data due to the maintenance of constant controlled conditions) in comparison with openfield system and pot experiments (Figure 9). The authors cultivated seeds [21][22][23], shoot apexes [48], shoot apical meristem [49], and callus [50][51][52][53] as an explant source under salinity treatments in vitro. The disadvantage of seeds as an explant source is high heterogeneity, as well as greatly differ in the uniformity of germination capacity and germination energy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies carried out to testing of tomato salinity tolerance during germination of non-sterile seeds under stress treatment [21][22][23] or aseptically seed germinated on culture media, containing various NaCl or Na 2 SO 4 concentrations [24][25][26][27]. However, even high-quality seeds greatly differ in the uniformity of germination capacity and germination energy.…”
Section: Introductionmentioning
confidence: 99%